Utility of magnetic resonance imaging for suspected appendicitis in pregnant women - Theilen, Lauren H.; Mellnick, Vincent M.; Longman, Ryan E.; Tuuli, Methodius G.; Odibo, Anthony O.; Macones, George A.; Cahill, Alison G. (American journal of obstetrics and gynecology, 2015)
The purpose of this study was to estimate the rate and risk of appendix nonvisualization and alternative diagnoses made with magnetic resonance imaging (MRI) for suspected appendicitis in pregnant women. We performed a retrospective cohort study of consecutive pregnant women who underwent MRI for suspected appendicitis at a single center from 2007-2012. Data on clinical presentation, imaging, and surgical pathologic evidence were extracted from electronic medical records. Odds ratios estimated risk factors for nondiagnosis. Radiologic diagnoses were identified, and rates of diagnoses were calculated. Subgroup analysis was performed among women who underwent initial imaging with ultrasound scanning. Over the 5-year period, 171 pregnant women underwent MRI for suspected appendicitis. The rate of nonvisualization was 30.9% (n = 53). Of the remaining 118 women with a visualized appendix, 18 women had imaging findings that were consistent with appendicitis and underwent appendectomy. Twelve cases of appendicitis were confirmed on pathologic evaluation (66.7%). Women with nonvisualization of the appendix on MRI were more likely to be beyond the first trimester (odds ratio, 2.1; 95% confidence interval, 1.0–4.5). Seventy-four women had disease diagnosed on MRI (43.3%). In the group of 43 women who had a nondiagnostic ultrasound scanning before the MRI, the rate of subsequent diagnostic MRI was 65% (n = 28). MRI yields a high diagnostic rate and accuracy in pregnant women with suspected appendicitis and provides alternative diagnoses to guide further management. Given the high rate of appendix nonvisualization on ultrasound scanning that has been reported in the literature, we recommend MRI as the imaging modality of choice for this population in settings in which MRI is readily available.